Protecting ocean carbon through biodiversity and climate governance - Elsler, Laura G.; Oostdijk, Maartje; Levin, Lisa A.; Satterthwaite, Erin V.; Pinsky, Malin L.; Crespo, Guillermo Ortuño; Wisz, Mary S. (Frontiers in Marine Science, 2022)
Global policy goals for halting biodiversity loss and climate change depend on each other to be successful. Marine biodiversity and climate change are intertwined through foodwebs that cycle and transport carbon and contribute to carbon sequestration. Yet, biodiversity conservation and fisheries management seldom explicitly include ocean carbon transport and sequestration. In order to effectively manage and govern human activities that affect carbon cycling and sequestration, international biodiversity and climate agreements need to address both biodiversity and climate issues. International agreements that address issues for climate and biodiversity are best poised to facilitate the protection of ocean carbon with existing policies. The degree to which the main international biodiversity and climate agreements make reference to multiple issues has however not been documented. Here, we used a text mining analysis of over 2,700 binding and non-binding policy documents from ten global ocean-related agreements to identify keywords related to biodiversity, climate, and ocean carbon. While climate references were mostly siloed within climate agreements, biodiversity references were included in most agreements. Further, we found that six percent of policy documents (n=166) included ocean carbon keywords. In light of our results, we highlight opportunities to strengthen the protection of ocean carbon in upcoming negotiations of international agreements, and via area-based management, environmental impact assessment and strategic environmental assessment.